2020
DOI: 10.1080/17430437.2020.1804113
|View full text |Cite
|
Sign up to set email alerts
|

How do perceptions of non-mega sport events impact quality of life and support for the event among local residents?

Abstract: Previous research has overlooked the influence of non-mega sport events on local residents' perceptions of quality of life and their attitude toward the hosting of events; in particular, there is a major research void in understanding residents' opinions in Chinese cities that are making escalated efforts in staging small to medium size sport events. This study examined the relationships among the perceived impacts of sport event, quality of life, and event support of local residents at a marathon event in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
1
13
0
3
Order By: Relevance
“…For example, Parra-Camacho et al (2020) focused on residents who participated in a triathlon in Valencia, Spain, and explored three social impacts: social development and human capital, sport participation and city image, and economic development. Another study that conducted a questionnaire survey with spectators of Wuhan Marathon in China revealed that, social impacts had a significant positive impact on the quality of life and event support (Duan et al , 2020). Further, prior research discussed that social development and human capital allow residents to have a sense of well-being and have the opportunity to relate to new people as well as include disadvantaged groups and those at risk of social exclusion (Parra-Camacho et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Parra-Camacho et al (2020) focused on residents who participated in a triathlon in Valencia, Spain, and explored three social impacts: social development and human capital, sport participation and city image, and economic development. Another study that conducted a questionnaire survey with spectators of Wuhan Marathon in China revealed that, social impacts had a significant positive impact on the quality of life and event support (Duan et al , 2020). Further, prior research discussed that social development and human capital allow residents to have a sense of well-being and have the opportunity to relate to new people as well as include disadvantaged groups and those at risk of social exclusion (Parra-Camacho et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Residents' well-being has been the focal point for local authorities and central governments during discussions on public policymaking. Evaluating the effects of sporting events is crucial because residents are key stakeholders of these events (Oshimi and Harada, 2019), and maintaining their support ensures the events' continued success (Duan et al , 2020; Theodorakis et al , 2015). Notably, although hosting an event is expected to enhance residents' subjective well-being and quality of life (Yolal et al , 2016), more research is needed on day-to-day effects on the local community (Duan et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Los eventos deportivos son objeto de numerosas investigaciones desde diversas áreas de estudio desde su análisis económico, social y medioambiental, incluso desde otras áreas como la preparación física y nutricional (e.g., Martínez et al, 2019). Aunque la mayoría de los trabajos sobre el impacto social han centrado su interés en los mega eventos deportivos (campeonatos del mundo de fútbol y Juegos Olímpicos) (Chen et al, 2018), cada vez se observan más contribuciones sobre otros eventos deportivos de menor escala (e.g., Chen et al, 2018;Duan et al, 2020;Hautbois et al, 2020;Parra-Camacho et al, 2020;Sánchez-Sáez et al, 2018;Taks, 2013;Vegara-Ferri et al, 2020).…”
Section: Introductionunclassified
“…Las aportaciones sobre los eventos de menor escala son escasas al compararlas con los trabajos realizados sobre los mega eventos. Algunos trabajos han analizado las relaciones entre los impactos percibidos y variables como el apoyo a la celebración del evento (Duan et al, 2020;Parra-Camacho et al, 2020), calidad de vida (Duan et al, 2020), satisfacción general de los residentes e intenciones futuras (Parra-Camacho et al, 2016;Vegara-Ferri et al, 2020). Estos trabajos han identificado algunos factores en los que se agrupan los indicadores asociados a los impactos de los eventos de menor escala.…”
Section: Introductionunclassified
See 1 more Smart Citation